Integrated assessment and adaptation to climate change impacts in the Peruvian Andes - Salzmann, N. (2009)
The Andes as mountain regions worldwide, provide fundamental resources, not only for the local population. Due to the topographic characteristics, the potential for natural hazards is higher than elsewhere. In these areas, assessments of climate change impacts and the development of adequate adaptation strategies therefore become particular important. The data basis, however, is often scarce. Moreover, perceptions of changes and needs are often divergent between national and local levels, which make the implementation of adaptation measures a challenge. Taking the Peruvian Andes as an example, this paper aims at initiating a discussion about scientific baseline and integrative concepts needed to deal with the adverse effects of climate change in mountain regions.